DNA Mini-Barcodes, a Potential Weapon for Conservation and Combating Illegal Trade of Pangolin. (May 2021) - Xie, Xuena; Ye, Haoting; Cai, Xuan; Li, Chan; Li, Fang; Tian, Enwei; Chao, Zhi
Background: Smuggling and illegal trade of pangolins and their scales has drastically reduced the wild population of pangolins. Accurate species identification is currently in urgent need as a powerful weapon for combating pangolin smuggling and trade and conserving the already endangered pangolin species. Aim of the study: To develop an efficient method based on DNA mini-barcodes for accurate pangolin species identification and authentication of processed pangolin scales against the non-target species. Materials and methods: The primers for amplifying the DNA mini-barcodes were designed based on cytochrome C oxidase subunit I (COI) gene fragments. The mini-barcodes were compared with the two universal barcodes (COI and Cytb) for performance in pangolin species identification by calculating the Kimura-2-parameter (K2P) distance, assessing the clustering dendrogram, and analyzing the BLAST similarity and barcoding gap. The accuracy of the three barcodes was also compared for authentication of pangolin scales against non-target species. Results: Comparison of the three barcodes showed that the mini-barcode form COI had the highest amplification success rate (100%) and high variable sites (40.0%), with the ratio of mean inter- to intraspecific distance ratio was 25 and a distinct DNA barcoding gap. In the neighbor-joining (NJ) tree constructed based on the mini-barcode regions, each species of the pangolin family formed an obvious clade respectively, and the clades were all separated from those of the non-target species, indicating that the genetic information in the mini-barcode was sufficient for species identification. Conclusion: The DNA mini-barcodes based on COI gene fragments provide an effective and accurate method for identification of pangolin species and authentication of pangolin scale products.